First detection of Dickeya fangzhongdai in Italy: double-edged role from virulent on vegetables to potent VOC-mediated anti-Xylella fastidiosa activity - Sabri, Miloud; El Handi, Kaoutar; Mektoubi, Khaoula; Trani, Antonio; Cara, Orges; Elbeaino, Toufic (Frontiers in Microbiology, 2025)
In this study, we report the first detection of Dickeya fangzhongdai (D. fangzhongdai) in Italy, which was isolated from an asymptomatic cauliflower plant in Valenzano (Apulia region), as part of an effort to isolate antagonistic bacteria against Xylella fastidiosa subsp. pauca (Xfp). Results of the preliminary antagonistic screening showed that one isolate (C7) has a strong activity against Xf on BCYE agar plates. The Illumina whole-genome sequencing and bioinformatic analysis showed that C7 genome consists of a single circular chromosome of 5,045,655 bp in size, with an average nucleotide identity (ANI) exceeding 98% when compared with other D. fangzhongdai strains reported in the GenBank; thereby confirming its taxonomic allocation within the D. fangzhongdai species. Furthermore, multi-locus sequence analysis employing concatenated sequences of the atpD, gyrB, infB, and rpoB genes showed that the strain C7 is phylogenetically close to D. fangzhongdai strain B16 from Slovenia (acc. no: NZ_CP087226). The strong antagonistic activity of C7 against Xf was also observed under physically separated conditions using a cut agar barrier, suggesting the involvement of volatile antimicrobial compounds (VOCs). Thus, headspace solid-phase microextraction and gas chromatography coupled with mass spectrometry (SPME/GC–MS) analysis revealed that the strain C7 emits 17 distinct VOCs during incubation in YPG broth, suggesting that strain C7 employs VOC-mediated inhibition as a defense mechanism to suppress bacterial competitors. Pathogenicity assessment showed that strain C7 induces severe soft rot in potato tubers, onion bulbs, and pear fruits, as well as, for the first time, causes browning of vascular tissues in cauliflower plants and blackleg in Havana tobacco plants. The prior detection of D. fangzhongdai in the Netherlands and its present identification in Italy on new hosts (cauliflower and tobacco) raise significant concerns about its further establishment, expanded host range, and phytosanitary implications for European agriculture.